2021
DOI: 10.1002/ehf2.13227
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three major co‐morbidities on quality of life and outcome of patients with heart failure with reduced ejection fraction

Abstract: Aims Diabetes mellitus, chronic obstructive pulmonary disease, and chronic kidney disease are prevalent in patients with heart failure with reduced ejection fraction (HFrEF). We have analysed the impact of co-morbidities on quality of life (QoL) and outcome. Methods and results A total of 397 patients (58.8 ± 11.0 years, 73.6% with New York Heart Association functional class ≥3) with stable advanced HFrEF were followed for a median of 1106 (inter-quartile range 379-2606) days, and 68% of patients (270 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To our best knowledge, this is the first study that analyzed the QoL with respect to MET treatment using a validated tool 45 . It has been recently demonstrated that QoL in HF patients is driven by HF itself, not by associated comorbidities 46 . MET-induced improvement in myocardial efficiency 29 suggests that the effect of MET on QoL in HF is rather due to an improvement in HF, not due to improvement in blood glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, this is the first study that analyzed the QoL with respect to MET treatment using a validated tool 45 . It has been recently demonstrated that QoL in HF patients is driven by HF itself, not by associated comorbidities 46 . MET-induced improvement in myocardial efficiency 29 suggests that the effect of MET on QoL in HF is rather due to an improvement in HF, not due to improvement in blood glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with worse renal function, worse side effect profile, greater symptoms for a given degree of cardiac impairment, and higher hospitalization and mortality rates. 18 , 19 , 20 Partly as a result of this higher underlying risk, the benefits of optimal medical therapy are greater in patients with Type 2 diabetes mellitus, 21 and the drive to achieve optimization is more pressing. Despite this, the gap in HFrEF treatment optimization is similar in patients with and without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a co‐morbidity in 30–40% of all patients with HFrEF and considerably worsens the prognosis. It is associated with worse renal function, worse side effect profile, greater symptoms for a given degree of cardiac impairment, and higher hospitalization and mortality rates 18–20 . Partly as a result of this higher underlying risk, the benefits of optimal medical therapy are greater in patients with Type 2 diabetes mellitus, 21 and the drive to achieve optimization is more pressing.…”
Section: Discussionmentioning
confidence: 99%
“…The shared risk factors in patients with concomitant HF and COPD include aging, smoking, and systemic inflammation [10] and may partly explain their frequent association. However, other comorbidities share the common mechanisms of HF and COPD and possibly impact the standard maintenance medication regimen, thereby contributing to the overall prognosis [11]. Furthermore, as they manifest the same symptoms, COPD is often underdiagnosed in patients with HF.…”
Section: Introductionmentioning
confidence: 99%